Mah Heng Motor Enterprise Full Stack Management System - LUU, WEI CHEK; Mohd Zaki Mohd Salikon (Applied Information Technology And Computer Science, 2025)
Mah Heng Motor Enterprise is a company responsible for repairing and selling motor parts and accessories. For instance, sell tayar, oil, chain, light bulb, windscreen and so on. Currently, the existing database management process for Mah Heng Motor Enterprise still relies on manual processes and documentation to manage its business operation. However, there have several issues encountered in the existing system on managing the stocks and reports. In order to assist in overcoming these constraints, the suggested system will be developed. The public website, login page module, manage customer, manage supplier, invoice management, stock management, sales service, and generate report modules are the eight modules that make up the proposed system. This system using waterfall model methodology to develop. The proposed system will be written by HTML,CSS,JAVA SCRIPT and PHP programming language that running on the Visual Studio mechanisms and SQL server will be the database server. When the developed system is released, Mah Heng Motor Enterprise will be the target to participate in the user acceptance test (UAT). The expected outcome for the proposed system is able to resolve the issues for the existing system such as stock data well-organized and generate the sales report. It will help Mah Heng Motor Enterprise manages the stock information in proper way.